Lala Land: A Discursive Ethnography of Professional Commercial Photographers - Craig, Trigg (Curtin University, 2016)
This research investigates the professional practice of commercial photography with prominence given to the significance of the relationship between the photographers’ professionalism and commerciality. It is based on evidence that emerged during two years of ethnographic fieldwork in Perth, Western Australia between August 2001 and January 2003. Having shifted from the analysis of photos to the analysis of practice, it draws on Foucault’s conception of discourse to analyse the knowledge, materiality and power that constitutes this relationship.